Chemical Composition, Antimicrobial and Insecticidal Activities of Flowers Essential Oils of Alpinia zerumbet (Pers.) B.L.Burtt & R.M.Sm. from Martinique Island. Issue 4 (20th March 2017) - Kerdudo, Audrey; Ellong, Emy Njoh; Burger, Pauline; Gonnot, Vanessa; Boyer, Laurent; Chandre, Fabrice; Adenet, Sandra; Rochefort, Katia; Michel, Thomas; Fernandez, Xavier
Abstract : Alpinia species, used as ornamental plants and flavoring agents, are renowned for their therapeutic properties and their subsequent use in traditional medicines throughout the world. Alpinia zerumbet (Pers .) B.L.Burtt & R.M.Sm . is the most common Alpinia species encountered in Martinique. Several essential oils (EOs) obtained by hydrodistillation of A . zerumbet flowers collected in various locations on the island at different seasons were analysed to evaluate the influence of the collection period and area on the EOs' chemical compositions and to assess their bioactivity. A combination of GC‐FID and GC/MS techniques was used to examine the volatile constituents, leading to the identification of a total of 71 components accounting for 97.8 – 99.3% of the respective total GC‐FID areas: among them, nineteen compounds were characterized for the first time in A . zerumbet EOs. The antimicrobial activity of these EOs was assessed against eight bacterial, yeast and fungal strains and two multi‐resistant strains: some significant bacteriostatic and fungistatic activities of A . zerumbet flower oils were evidenced. Finally, an interesting insecticidal activity of the flower EO was highlighted for the first time against Aedes aegypti . Abstract :